Design of a website on nutrition and physical activity for adolescents: results from formative research. - Thompson, D.; Cullen, K.; Boushey, Carol; Konzelmann, K. (Journal of Medical Internet Research, 2012)
Teens do not meet guidelines for healthy eating and physical activity. The Internet may be an effective method for delivering programs that help them adopt healthy behaviors. To collect information to design content and structure for a teen-friendly website promoting healthy eating and physical activity behaviors. Qualitative research, encompassing both focus group and interview techniques, were used to design the website. Participants were 12-17 year olds in Houston, Texas, and West Lafayette, Indiana. A total of 133 participants took part in 26 focus groups while 15 participated in one-on-one interviews to provide guidance for the development of teen-friendly content and structure for an online behavior change program promoting healthy eating and physical activity to 12-17 year olds. The youth made suggestions to overcome common barriers to healthy eating and physical activity. Their feedback was used to develop "Teen Choice: Food & Fitness," a 12-week online behavior change program, populated by 4 cartoon character role models. It is critical that members of the target audience be included in formative research to develop behavior change programs that are relevant, appealing, and address their needs and interests.